Ukraine: ‘Callous disregard for human life’ of Russian forces’ response to Kakhovka dam destruction compounded by its disastrous effects upstream - Amnesty International (Amnesty International, 2023)
As the consequences of the Kakhovka dam destruction continue to unfold, the occupying Russian forces have been endangering lives in flood-afflicted areas following the destruction of the dam, while upstream water shortages and an upheaval  of livelihoods point to an impending ecological and economic disaster, Amnesty International said today.
Keywords: 2023-06 June